SCHOOL POLICY STRATEGIES AND CHALLENGES IN PREPARING DIGITAL LITERACY AND CODING LEARNING IN THE INDEPENDENT CURRICULUM ERA AT SDN PINGGIR PAPAS II - Ahmad Fauzan; Ali Armadi; M. Misbahudholam Ar (World Psychology, 2026)
The development of information and communication technology in the 21st century requires the Indonesian education system to undergo profound reforms, one of which is through the implementation of the Independent Curriculum, reinforced in Permendikdasmen Number 13 of 2025. This curriculum prioritizes the development of holistic competencies, including digital literacy and coding learning as a foundation for computational, logical, and problem-solving thinking skills. This study aims to describe the school policy strategy, challenges, and efforts to overcome them at SDN Pinggir Papas II. The study used a qualitative, descriptive case study approach. Data collection was conducted through interviews, observations, and documentation with the principal, teachers, and students. The results show that the school has implemented strategies such as developing internal policies, allocating lesson hours, an unplugged approach, and limited facility support. The main challenges include limited infrastructure, developing teacher competencies, and disparities in student access to technology. The school responded through flexible methods and simplifying materials. In conclusion, the policy has been implemented but is not optimal, so ongoing training and more equitable facility support are needed.